A Content Analysis Original Scientific Papers of Physical Activity of Old People Published in Journal of Anthropology of Sport and Physical Education - Ivan Vukovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The purpose of this paper has been to collected researches that have been published in JASPE journal that is showing the study of the physical activity of old people between the ages of 50 to 69. They were placed in two groups, first group was people from 50 to 59 age and second group was people with 60 to 69 ages. On these five papers that have been collected, from one to another there have been different views but all of them have had the same point and the same idea. The main point of all these papers is that physical activity must be risen to a higher level. Every research has been done by surveys and old people were giving their answers according to that what they were doing in the last 7 days for example; at work, at home, in their free time, etc. Also, all those activities had 3 groups, hard activity, medium activity, light activity. Results have been showed that physical activity of old people was on quite good level, but that level is not enough. There was a difference, between two groups. Results showed that younger group was more active than older one.